s=c(A=B)find c

To find the value of c, we can rearrange the equation s = c(A = B).

1. Start by substituting the value of the expression (A = B) into the equation.
s = c(True) (if A and B are equal)
s = c(False) (if A and B are not equal)

2. Simplify the expressions:
If A is equal to B, then (A = B) evaluates to True.
If A is not equal to B, then (A = B) evaluates to False.

3. Substitute these simplified forms back into the equation:
If A = B, then s = c(True)
If A ≠ B, then s = c(False)

4. From this analysis, we can conclude that the value of c depends on whether A and B are equal or not.

Therefore, without additional information about the values of A and B or the value of s, it is not possible to determine the specific value of c.